III Cycle Science Education and Care for Students with Visual Impairment Through Cognitive Stimulation Strategies Based on Universal Design for Learning in Costa Rica - Vásquez-Solís, Joselyn (2026)
Introduction. This article originates from research conducted to obtain the Licenciatura degree in Science Education from the Universidad Nacional, Costa Rica. Objective. To analyze the pedagogical mediation strategies to approach different science topics in the third cycle, as well as teachers’ knowledge of Cognitive Stimulation Strategies (CSS) based on Universal Design for Learning (UDL) for students with visual impairments. Methodology. The study was conducted within a naturalistic paradigm, using a qualitative approach and a phenomenological design. The research involved three secondary schools and included a sample of nine science teachers and three students with visual impairments. Semi-structured interviews were conducted to identify pedagogical mediation strategies and the implementation of UDL. A didactic proposal incorporating CSS was evaluated through a second semi-structured interview with the students, as well as a questionnaire administered to the teachers and the science advisor at the Centro Nacional de Educación Helen Keller (CNEHK). Results. The study identified pedagogical mediation strategies, teachers’ knowledge and implementation of the DUA, and the educational supports provided to students with visual impairments. The evaluation of the proposal revealed that 82% of teachers considered the EECs to be very effective because they facilitate content comprehension in an engaging way, making them important learning enhancers. Conclusions. Ongoing training, reflective practice, and awareness-raising initiatives are critical to promoting strategies from an inclusive perspective.